(untitled) (JURNAL PROTEKSI KESEHATAN, 2022)
Prevention and control of nutritional problems of pregnant women is important for fetal growth and development during the womb and after birth. Pregnant women with low economic status and food security in food insecure households will be at risk of being born with low birth weight. The purpose of the study was to describe the economic status, household food security, intake, and nutritional status of pregnant women in Pekanbaru City. This type of research is using a cross sectional survey approach design. Data collection was carried out using the Cluster Random Sampling Technique which was carried out at 12 Puskesmas in Pekanbaru City with a sample size of 221 pregnant women. Measurements were made with interviews related to the identity of the respondents, economic status and household food security; 2x24 hour recall to assess intake, and anthropometry to assess the nutritional status of pregnant women. The results showed that there were 25.2% of pregnant women in the poor category; 19.0% are food insecure without hunger; 64.7% of pregnant women have less energy intake, 56.6% of pregnant women have more nutritional status.